Chat software to improve student interaction in online classrooms - Marwa Abdulameer Oudah, Maryam Abdulameer Oudah Ahlulbait (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Due to the health concerns regarding COVID-19 which lead to make governments imposes partial or complete lockdown sometimes. Which make universities, colleges and high schools relying on online classes as a communication tool between lecturers and students. There are big number of lecturers complain about lack of student engagement with the online classes. We proposed an anonymous chat system to improve students’ interaction and engagement in the online classes. We believe that system will motivate the students to ask more questions during the discussion sessions and beef up the student engagement with online class.